The Chinese version of patient-doctor-relationship questionnaire (PDRQ-9): Factor structure, validation, and IRT psychometric analysis - Wang, Yufei; Wu, Aoxue; Jiang, Yinan; Duan, Yanping; Geng, Wenqi; Wan, Lin; Li, Jiarui; Du, Jianhua; Hu, Jiaojiao; Jiang, Jing; Shi, Lili; Wei, Jing (Frontiers in Psychiatry, 2023)
Objective: This study examined the psychometric properties of the Chinese version of the Patient-Doctor-Relationship Questionnaire-9 item (PDRQ-9) scale among general hospital inpatients in China. Methods: A total of 203 participants responded to the survey, of which 39 completed retest after 7 days. Factor analyses were used to test the construct validity of the scale. Convergent validity was evaluated by the correlation between PDRQ-9 and PHQ-9. Both multidimensional item response theory (MIRT) and unidimensional item response theory (IRT) framework were used to estimate the parameters of each item. Results: The two-factor model of relationship quality and treatment quality was supported (χ2/df=1.494, GFI=0.925, RMSEA=0.071, RMR=0.008, CFI=0.985, NFI=0.958, NNFI=0.980, TLI=0.980, IFI=0.986). The PDRQ-9 and both subscales showed significant correlation with PHQ-9 (r=-0.196~-0.309) and good internal consistency (Cronbach's alpha = 0.865~0.933). ANCOVA analysis adjusted with age revealed significant difference in PDRQ-9 ratings between patients with or without significant depressive symptoms (P = .019). The 7-day test-retest reliability of the scale was 0.730. The MIRT model of full scale and IRT models of both subscales showed high discrimination of all items (a=2.46~38.46), and the test information within the range of low-quality relationship was relatively high. Conclusion: The Chinese version of PDRQ-9 is a valid and reliable rating scale, which can measure the doctor-patient relationship among Chinese patients.